Tribological performance of differential gear end-face sliding on washer with a radial groove. (March 2018) - Yuan, Wei; Dong, Guangneng; Guo, Qianjian; Sui, Wentao; Zhang, Leian; Yuan, Weiyun
Abstract: Effects of a radial groove perpendicular to relative sliding direction on the tribological properties of the differential gear end-face on the corresponding thrust washer, were experimentally investigated under both sufficient and insufficient lubrication. A radial groove was artificially introduced into the thrust washer. The monitored friction force signals were analyzed by discrete wavelet transform. The wear scar of thrust washers were scanned with scanning electron microscope. The wear particles were collected and identified in the tests under insufficient lubrication. Results indicated that (i) the radial groove tended to decrease the friction force at the running-in period and to cause several fluctuation of approximate 5 (A5) of the friction force at the test beginning time, and the amplitudes of detail 5 signals reflected the performance deterioration of the thrust washer after a specific operating period under sufficient lubrication; (ii) the amplitude of the friction force was reduced and the values of the pulsation of A5 gradually increased before the friction failure time under insufficient lubrication; (iii) with the effect of the radial groove, non-contact area and smooth surface area were found in the groove regions of the washer under sufficient lubrication, and shallow and narrow plowing grooves on the washer's wear scar were the dominant wear morphologies and the percentages of irregular and elongated particles were significantly high under insufficient lubrication. Highlights: Tribological performance of surface-contact friction pairs with a radial groove were assessed. The friction state is unstable at the beginning with a groove on washer. Groove can improve tribological performance at running-in period. Wear particles are likely to drop into the radial groove. More irregular and elongated particles emerged with a groove effect.